2013
DOI: 10.1371/journal.pone.0058519
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Size Variability in Deep-Sea Lanternfishes (Myctophidae): An Ecological and Phylogenetic Study

Abstract: One of the most common visual adaptations seen in the mesopelagic zone (200–1000 m), where the amount of light diminishes exponentially with depth and where bioluminescent organisms predominate, is the enlargement of the eye and pupil area. However, it remains unclear how eye size is influenced by depth, other environmental conditions and phylogeny. In this study, we determine the factors influencing variability in eye size and assess whether this variability is explained by ecological differences in habitat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 53 publications
7
61
0
Order By: Relevance
“…Seapy (1990) found that larger species offshore of Oahu migrated to deeper waters during the daytime. Similar trends of larger taxa with depth have been found in other mesopelagic zooplankton (Dai et al 2017), and larger eyes relative to body size are thought to in crease photon capture (and hence detection of predators and prey) in deeper dwelling mesopelagic fishes (de Busserolles et al 2013). …”
Section: Deep Water Diurnal Migrationsupporting
confidence: 59%
“…Seapy (1990) found that larger species offshore of Oahu migrated to deeper waters during the daytime. Similar trends of larger taxa with depth have been found in other mesopelagic zooplankton (Dai et al 2017), and larger eyes relative to body size are thought to in crease photon capture (and hence detection of predators and prey) in deeper dwelling mesopelagic fishes (de Busserolles et al 2013). …”
Section: Deep Water Diurnal Migrationsupporting
confidence: 59%
“…L. alatus and L. parvicauda, indicating a higher acuity in the centro-lateral visual field thereby allowing the fish to perceive signals in a large part of its monocular field of view, suggesting that these species are visual generalists. In addition to the generalist specialization, L. parvicauda does not appear to possess a very sensitive visual system due to its relatively small eyes [de Busserolles et al, 2013] and low summation ratios (around 20: 1 in the peak area and 50: 1 in the periphery) compared to other myctophids (i.e. M. brachygnathum 200: 1 in the peak area and 500: 1 in the non-specialized region) [de Busserolles et al, 2014b;this study].…”
Section: Ecological Significance Of the Retinal Specializations In Lamentioning
confidence: 89%
“…Furthermore, most species possessing an elongated area are also known to be surface migrants and have been recorded in the first few metres of water at night (i.e. Myctophum sp., Symbolophorus sp., D. laternatus [de Busserolles et al, 2013]), where a weak visual horizon would be formed by the downwelling light emitted by the moon and stars or by the air-water interface, explaining the need for a streaklike elongated area in these species.…”
Section: Inter-specific Differences In Retinal Specialisations In Lanmentioning
confidence: 99%
See 1 more Smart Citation
“…Like most mesopelagic fishes, lanternfishes (Myctophidae) possess several visual adaptations for life in the mesopelagic zone that serve to increase the sensitivity of the eye and optimise photon capture [de Busserolles et al, 2013[de Busserolles et al, , 2014a. Lanternfishes generally lack cones and possess a single rod photoreceptor class with a peak spectral absorption tuned to the blue-green region of the visible spectrum [Partridge et al, 1992;Douglas and Partridge, 1997;Turner et al, 2009].…”
mentioning
confidence: 99%